2017
DOI: 10.1097/mlr.0000000000000712
|View full text |Cite
|
Sign up to set email alerts
|

Association of the Affordable Care Act With Smoking and Tobacco Treatment Utilization Among Adults Newly Enrolled in Health Care

Abstract: Objectives To examine rates of smoking and tobacco treatment utilization by insurance coverage status (Medicaid, commercial, exchange) among newly enrolled patients in the post ACA era. Methods We examined new members who enrolled in Kaiser Permanente Northern California (KPNC) through Medicaid, the California exchange, or non-exchange commercial plans (N=122,298) in the first six months of 2014 following ACA implementation. We compared these groups on smoking prevalence and tested whether smokers in each gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 19 publications
(17 reference statements)
0
22
0
Order By: Relevance
“…35 Additionally, cessation treatments not only can be effective without adversely impacting treatment outcomes for other substance abuse, but smoking cessation has a positive relationship with other substance abuse outcomes. 36 …”
Section: Discussionmentioning
confidence: 99%
“…35 Additionally, cessation treatments not only can be effective without adversely impacting treatment outcomes for other substance abuse, but smoking cessation has a positive relationship with other substance abuse outcomes. 36 …”
Section: Discussionmentioning
confidence: 99%
“…22 Our results are consistent with a recent study in Northern California that showed that Medicaid enrollees were more likely to use smoking cessation treatment, relative to smokers enrolled in nonexchange commercial plans. 23 People who shop for health insurance on healthcare.gov are asked whether they smoke cigarettes. It is possible that this question might prompt adults to start contemplating smoking cessation during the Medicaid enrollment process.…”
Section: Discussionmentioning
confidence: 99%
“…Young-Wolff et al (2017) use a pre-post design to provide evidence that cessation medication use increased postexpansion among Medicaid enrollees in the Kaiser Permanente Northern California system.…”
mentioning
confidence: 99%